2021
DOI: 10.1002/eat.23523
|View full text |Cite
|
Sign up to set email alerts
|

Using network analysis to compare diagnosis‐specific and age‐specific symptom networks in eating disorders

Abstract: Objective: The network theory of mental disorders conceptualizes eating disorders (EDs) as networks of interacting symptoms. Network analysis studies in EDs mostly have examined transdiagnostic and/or mixed age samples. The aim of our study was to investigate similarities and differences of networks in adolescents and adults with anorexia nervosa (AN) or bulimia nervosa (BN).Method: Participants were 2,535 patients (n = 991 adults with AN, n = 821 adolescents with AN, n = 473 adults with BN, and n = 250 adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 54 publications
1
34
1
Order By: Relevance
“…comparison of estimated network structures among clinical and nonclinical (Vanzhula et al, 2019), ethnic minority women (Perez et al, 2021), men and women (Perko et al, 2019), across developmental stages (Calugi et al, 2020; Christian et al, 2020; Schlegl et al, 2021), and across different duration of illness (Christian et al, 2021);…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…comparison of estimated network structures among clinical and nonclinical (Vanzhula et al, 2019), ethnic minority women (Perez et al, 2021), men and women (Perko et al, 2019), across developmental stages (Calugi et al, 2020; Christian et al, 2020; Schlegl et al, 2021), and across different duration of illness (Christian et al, 2021);…”
Section: Resultsmentioning
confidence: 99%
“…The JGL has been applied in the EDs research as well. Schlegl et al (2021) used the FGL with k -fold cross-validation for parameter selection to estimate four different networks, one for each of the following groups: adolescents with AN, adults with AN, adolescents with BN, and adults with BN. Similarly, Smith et al (2020) used the FGL to estimate and compare distinct networks from samples corresponding to either of the following groups: outpatients without ED diagnosis, outpatients with a lifetime attempt of suicide, and people with a current ED diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, older participants may have been less reliable in recalling OCPD traits from their childhood in comparison to younger participants, which may have differentially impacted the reliability of OCPD traits. We choose to retain these participants to maintain the diverse age range of our sample given the current under-representation of older age groups in previous research (Pike et al, 2013) and on the basis of Schlegl et al's (2021) study who found no significant differences in the ED symptom network between adults and adolescents with AN and BN.…”
Section: Limitationsmentioning
confidence: 99%
“…In recent years, psychological network analyses have been performed in patients with diagnosed eating disorders including anorexia nervosa and bulimia nervosa with the aim to identify central symptoms of the eating disorder pathology. Studies including a variety of eating disorder symptoms in their network analysis found that shape and weight concerns, desiring weight loss, desire to be thinner, feeling ineffective, worries that feeling will get out of control and guilt after overeating were the most central symptoms [25][26][27]. Other studies on eating disorder patients which additionally included general psychopathology showed that depressive and anxiety symptoms, interpersonal sensitivity and personal alienation had the highest centrality in the network [28,29].…”
Section: Introductionmentioning
confidence: 99%